Persepsi Konsumen terhadap Bauran Pemasaran Perusahaan Produsen Kerudung Rabbani di Wilayah Yogyakarta - Salihah Khairawati (At-Tauzi : Jurnal Ekonomi Islam, 2017)
The purpose of this research is to describe consumers perception in marketing mix of Rabbani’s coorporation. The marketing mix elements that used are product, price, promotion and distribution. This research uses primary data with a help of questionnaire. The total respondent of this research is 100 people by using purposive sampling method. Descriptif analysis used to analyze each elements. The results showed that most of respondents give positive respond to all elements, in another word the perceptions of respondent are good about Rabbani’s marketing mix.